Optimization of the production of grade A liquid smoke from Patchouli solid residue using a distillation-adsorption process - Zainuddin Ginting; Adi Setiawan; Khairul Anshar; Ishak Ibrahin; Jalaluddin; Indri Riski Hasanah; Fitriyaningsih; Zetta Fazira (AIMS Environmental Science)
Patchouli cultivation in Lhokseumawe, Aceh Province, produces a significant amount of biomass, with approximately 96%–98.5% of the raw material ending up as solid residue after the oil distillation process. This waste is often discarded or burned, leading to environmental problems. However, this residue is rich in compounds derived from the breakdown of lignocellulose and can be pyrolyzed to produce liquid smoke. Liquid smoke contains valuable phenols, acids, and carbonyls but may also generate harmful byproducts such as polycyclic aromatic hydrocarbons (PAHs). This study aimed to optimize the production of grade A liquid smoke through purification using a distillation and adsorption process. Pyrolysis of patchouli residue was conducted at 400 ℃ to produce liquid smoke. Furthermore, the raw liquid smoke was purified by distillation and adsorption. The distillation process was conducted at a temperature range (X1) of 150–200 ℃ for 30–90 min (X2). The weight of activated biochar used during the adsorption process varied between 5 and 15 g (X3). The experimental design was carried out using Design Expert version 13. Research findings indicate that the optimal condition for liquid smoke was achieved with the equation Y = 1.26 + 0.53X1 + 0.0319X2 + 0.8023X3 – (4.91X1)2 – (0.0015X2)2 – (0.2147X3)2 – 0. 0644 X1X2 – 0.0327X1X3 + 2.15X2X3. The best results were obtained at a distillation temperature of 175 ℃, a duration of 90 minutes, and using 13.4 g of activated carbon, which resulted in a high total phenol yield of 8.06%. The produced liquid smoke was classified as grade A, with a yield of 74.33%, a density of 0.9928 g/m³, a viscosity of 1.6203 cP, and a pH of 3.32. This research highlights an eco-friendly solution for valorizing patchouli waste, transforming it into a product with a wide range of applications as a food preservative, flavor enhancer, and medicinal agent.